Evidence for interlayer coupling and moiré excitons in twisted WS2/WS2 homostructure superlattices - Zheng, Haihong; Wu, Biao; Li, Shaofei; He, Jun; Chen, Keqiu; Liu, Zongwen; Liu, Yanping (Nano research, 2023)
The formation of moiré superlattices in twisted van der Waals (vdW) homostructures provides a versatile platform for designing the electronic band structure of two-dimensional (2D) materials. In graphene and transition metal dichalcogenides (TMDs) moiré systems, twist angle has been shown to be a key parameter for regulating the moiré superlattice. However, the effect of the modulation of the twist angle on moiré potential and interlayer coupling has not been the subject of experimental investigation. Here, we report the observation of the modulation of moiré potential and intralayer excitons in the WS 2 /WS 2 homostructure. By accurately adjusting the torsion angle of the homobilayers, the depth of the moiré potential can be modulated. The confinement effect of the moiré potential on the intralayer excitons was further demonstrated by the changing of temperature and valley polarization. Furthermore, we show that a detection of atomic reconstructions by the low-frequency Raman mapping to map out inhomogeneities in moiré lattices on a large scale, which endows the uniformity of interlayer coupling. Our results provide insights for an in-depth understanding of the behaviors of moiré excitons in the twisted van der Waals homostructure, and promote the study of electrical engineering and topological photonics.